Effect of peptide histidine valine on cardiovascular and respiratory function in normal subjects. Issue 10 (October 1988) - Chilvers, E R; Dixon, C M; Yiangou, Y; Bloom, S R; Ind, P W
Abstract : Non-adrenergic inhibitory nerves may have an important role in regulating airway calibre. A recently discovered peptide, peptide histidine valine, is a potent relaxer of airway smooth muscle in vitro and has been proposed as a possible neurotransmitter in this tissue. The cardiovascular and respiratory effects of graded infusions of this peptide (2.5-10 pmol kg-1 min-1) have been examined in six normal subjects in a placebo controlled, randomised double blind study. The mean (SEM) peak plasma concentration of peptide histidine valine during the highest infusion rate was 2392 (170) pmol/l, representing a 29 fold increase above the basal concentration. This was accompanied by flushing, a significant increase in heart rate of 28 (3.7) beats/min and skin temperature of 1.8 degrees (0.16 degrees) C, but no effect on systolic or diastolic blood pressure. Despite these high plasma concentrations of the peptide and the substantial tachycardia and increase in skin blood flow, there was no change in partial expiratory flow at 40% of vital capacity (Vp40) or in the airway response to inhaled histamine (geometric PD40 9.37 and 9.73 mumol during saline and peptide histidine valine infusion respectively). Although these findings provide no support for a physiological role of peptide histidine valine in controlling airway function in healthy subjects, important effects of locally released peptides in the vasoactive intestinal peptide family cannot be excluded.